SISTEM PERENCANAAN PRODUKSI DAN PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA PERUSAHAAN SUSU OLAHAN - Daddy Budiman; Rini Hakimi (Politeknik Negeri Padang, 2004)
Companies often have difficulties to make a choice in a raw material inventory. It is hard to decide the quantity of it. Another problem is difficult to match the needed and the purchasing of raw material. So, it is important to make a production planning and a controlling of raw material inventory. Brown’s Single Parametric Linear Method is used to predict the sales for the production planning and Economic Order Quantity Method is used to control the inventory. The prediction result is PT XYZ processing milk production will become 97045511 kg in 2002 with the total using of Full Cream Milk Powder (FCMP) is 3745957 kg and the using of Skim Milk Powder (SMP) is 2076774 kg. Total of ordering raw material based on EOQ method is 106346 kg for New Zealand’s FCMP in 15 times of ordering per year; 119889 kg of Australia’s FCMP in 18 times per year; 81113 kg. New Zealand’s SMP in 11 times of ordering per year; 91444kg Australia’s SMP in 13 times of ordering per year